Design of a low power wide-band high resolution programmable frequency divider. - Yu, X.P (IEEE Transactions on VLSI systems)
The design of a high-speed wide-band high resolution programmable frequency divider is investigated. A new reloadable D flip-flop for the high speed programmable frequency divider is proposed. It is optimized in terms of propagation delay and power consumption as compared with the existing designs. Measurement results show that an all-stage programmable counter implemented with this D flip-flop using the Chartered 0.18 μm CMOS process is capable of operating up to 1.8 GHz for a 1.8 V supply voltage and a 5.8-mW power consumption. By using this counter, an ultra-wide range high resolution frequency divider is achieved with low power consumption for 5-6-GHz wireless LAN applications.